Biology Laboratory-Based Learning for Promoting Scientific Explanation - Phrathep, O-Phart; Supautumporn, Nampung; Kaewdee, Sakolrat (An Online Journal of Education, 2026)
Scientific literacy has become a key competency in the 21st century as citizens are increasingly required to evaluate evidences and apply scientific knowledge to make decisions. In response to this demand, both the Next Generation Science Standards (NGSS) and the Programme for International Student Assessment (PISA 2025) have identified the ability to construct scientific explanations as an essential learning outcome. Despite global emphasis on this topic, studies conducted in Thailand consistently reveal unsatisfactory student performance in this area. This difficulty can be attributed, in part, to instructional practices that prioritize content memorization over the active construction of knowledge through empirical inquiry. Biology offers a particularly promising context for addressing this challenge. Biology engages students with life processes that are inherently familiar and observable. Many biological phenomena can be investigated directly or with minimal instrumentation, allowing students to collect meaningful empirical evidence and interpret it through biological principles. This accessibility positions biology laboratory activities as an effective vehicle for developing scientific explanation skills in an authentic and meaningful way. This article examines instructional approaches that leverage biology laboratory activities to foster students’ ability to construct scientific explanations. Specifically, it discusses the integration of inquiry-based learning with the Claims-Evidence-Reasoning framework as both an instructional and an assessment tool. Principles for laboratory design, instructional implementation, and student assessment are outlined to provide biology and science teachers with effective classroom practices.